Physical activity in periods of social distancing due to COVID-19: a cross-sectional survey - Martinez, Edson Zangiacomi; Silva, Fabricia Mabelle; Morigi, Thais Zanin; Zucoloto, Miriane Lucindo; Silva, Thaise Lucena; Joaquim, Anderson Gregorio; Dall'Agnol, Gabriela; Galdino, Guilherme; Zangiacomi Martinez, Maisa Oliveira; Silva, Wanderson Roberto da [UNESP] (Abrasco-assoc Brasileira Pos-graduacao & Saude Coletiva, 2020)
Physical inactivity and sedentary behavior are associated with poor physical and mental health. The article aims to assess the changes in the habits of the Brazilian participants engaged in physical activities in relation to their practices, due the measures of social distancing during the COVID-19 epidemic in 2020. The secondary objective was to describe their levels of anxiety and depression. The questionnaire used in this online survey included demographic information, questions about self-perceptions of the impact of the COVID-19 in the life routines and the 14-item Hospital Anxiety Depression Scale. A total of 1,613 adults completed the questionnaire between May 11 and 15, 2020. Of those, 79.4% reported that the measures to contain the epidemic had any impact on their physical activities, and many had to interrupt or decrease the frequency of their practices. Participants who felt a higher impact of quarantine on their physical activities tend to have higher prevalence of anxiety and depression symptoms. Individuals who practiced physical activities reported that social distance had a high influence on their practices. Furthermore, changes in these habits are associated with high levels of poor mental health.
Keywords: COVID-19; SARS-CoV-2; Physical activity; Social distancing; Mental health